A review of hydraulic jump properties on both smooth and rough beds in sloping and adverse channels - M. Palermo; S. Pagliara (Acta Scientiarum Polonorum. Formatio Circumiectus, 2017)
Hydraulic jump is a phenomenon which has received significant attention in recent years and it is still studied because of its capacity to dissipate a considerable amount of the flow energy. Nevertheless, the importance of the topic still requires significant efforts from the scientific community. Namely, the prediction of the main lengths of the hydraulic jump are still an open question, as the actual knowledge on the topic does not cover all the possible configurations and boundary conditions which can usually be found in practical applications. In particular, the effects of bed roughness, bed slope, channel geometry, and air concentration on the conjugate depths ratio are still not fully understood. The present paper aims to furnish a synthetic picture of the state of art regarding the hydraulic jump properties in a wide range of both boundary conditions and geometric configurations. In particular, the analysis will be focused on the effect of both relative roughness and bed slope on the conjugate depth ratio, including the effect of air entrainment on the estimation of the effective depth. Furthermore, some predicting relationships proposed by different authors will be compared and discussed.